The public rights to the sidewalk in a smart city framework: The case study of Surabaya - Siti Aminah (Masyarakat, Kebudayaan dan Politik, 2021)
The pedestrian transformation in Surabaya smart city system encountered critical problem for pedestrians because transformation as a public space has reduced citizens’ rights to the city. Dominant forces tend to subordinate street vendors or Pedagang Kaki Lima (PKL), who require public space. The city or urban government produces pedestrians as public spaces to support the ‘Smart City’ concept. This study explores the government’s ability to guarantee citizens’ rights to the city. In addition, this study seeks to observe the process of public space transformation in cities that implement smart city systems and analyze spatial street vendors’ practices in the pedestrian space. This research applies the right to cities and public space from a Marxian spatial perspective. This research is a case study that uses a qualitative method and interpretive analysis. Research findings indicate pedestrians’ paradox due to the government’s dispossession process to protect pedestrians through ‘furniturization’ policies that reduce smart city implementation. In conclusion, there are dynamics of spatial practice and social expression as pedestrian problems. The smart city system’s implementation causes the loss of fulfillment of the poor and street vendors’ needs and rights to participate inclusively in the social and political process in managing the city’s public spaces.